A kind of polymer clay stabilizer and preparation method thereof
By adjusting the molecular weight of the polymer and introducing new functional groups, low molecular weight and high cationic polymer chains are prepared, which solves the problem of poor performance of existing clay stabilizers in high temperature, low permeability and acid-base environments, and achieves better anti-swelling, flocculation and surfactivity, and expands its application conditions.
Patent Information
- Application Number
- CN202411571308.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Existing clay stabilizers exhibit impermissible erosion resistance, poor aging, poor temperature resistance and susceptibility to external environments in high-temperature, low-permeability and acid-base environments, resulting in poor results in oil and gas field mining.
By changing the molecular mass of the polymer and introducing new functional groups externally, the interaction force between ions and mineral particles is enhanced, low molecular weight and high cationicity polymer chains are prepared, and a hydrophobic layer is formed to inhibit the hydration and expansion of clay, and the clay stability is improved through electrostatic and hydrogen bonding effects.
It has achieved excellent anti-swelling, flocculation and surfactivity at low concentrations, improved the water resistance, high temperature resistance and acid and alkali resistance of clay stabilizers, and expanded its application conditions in oil and gas field mining.
Smart Images

Figure SMS_13 
Figure SMS_14 
Figure SMS_15
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field exploitation, and in particular to a polymer clay stabilizer and a preparation method thereof. Background Art
[0002] Clay stabilizers can be clearly divided into inorganic salts, cationic surfactants and organic cationic polymers according to their main components. Among them, inorganic salts, as non-permanent stabilizers, are limited in effectiveness by the formation water environment during oil production, especially the re-substitution of sodium ions, which will cause the ion concentration to decrease to a critical value, and the effect of stabilizing clay will be lost. In addition, this type of stabilizer has limited effect in preventing clay migration, and it cannot achieve the characteristics of multi-point adsorption.
[0003] On the other hand, cationic surfactants can be closely adsorbed on the surface of clay particles by dissociating surface-active cations in water, effectively neutralizing the negative charge carried by the clay, thus playing an important role as an anti-swelling agent. However, when cationic surfactants are used as clay anti-swelling agents, it is necessary to be vigilant about the potential risk of their easy reaction with anionic chemicals and the formation of precipitation. In addition, one of its significant disadvantages is that it can change the original water wettability of the reservoir to oil wettability, and this change will directly lead to a significant decrease in the relative permeability of water.
[0004] Organic cationic polymers are a type of polymer containing nitrogen, sulfur and phosphorus. Currently, polyquaternary ammonium salts are widely used in organic cationic polymers. After dissociation in water, these substances can produce high molecular cations with high positive charge, which can form multi-point adsorption effects with multiple clay particles at the same time. After adsorption occurs, a protective film will be constructed on the surface of the clay particles, effectively inhibiting the expansion and migration of the clay particles.
[0005] However, it is worth noting that polyquaternary ammonium salts generally face challenges such as not being able to withstand high temperatures and having limited long-term anti-swelling performance. In addition, most existing products are not suitable for low-permeability and ultra-low-permeability reservoir environments (reservoir permeability is between 0.001 and 0.005 μm). For such reservoirs, if the molecular weight of the injected clay stabilizer is too large, it will not only fail to achieve the expected anti-swelling effect, but may also block the formation pores due to the large size of the polymer, thereby causing serious damage to the formation permeability. Summary of the invention
[0006] The technical solution of the present invention aims at the performance defects of existing clay stabilizers such as poor erosion resistance, poor timeliness, poor temperature resistance and susceptibility to external environment, and provides a polymer clay stabilizer and a preparation method thereof.
[0007] The main purposes of the present invention are: 1. Strengthening the water resistance of the clay stabilizer to avoid water-sensitive damage to the reservoir.
[0008] 2. Optimize the clay stabilizer so that it has excellent anti-swelling and flocculation properties and surface activity at low concentrations.
[0009] 3. Adjust the surface properties of clay stabilizer in acidic and alkaline environments and expand the application conditions of clay stabilizer.
[0010] To achieve the above objectives, the present invention adopts the following technical solutions.
[0011] A method for preparing a polymer clay stabilizer comprises: (1) uniformly mixing an amide containing a carbon-carbon unsaturated bond, an anionic surfactant, a bioactive compound, a ketone compound and an initiator in proportion, heating for reaction, filtering for recrystallization, and drying to prepare a substrate precursor.
[0012] (2) The substrate precursor, the amino compound and the epoxy hydrocarbon compound are uniformly mixed in proportion and stirred continuously to prepare a polymer substrate.
[0013] (3) Mix the ammonium salt, metal ion chelating agent and azo initiator in proportion, stir and keep warm to prepare a modified solution.
[0014] (4) The polymer base material and the modified liquid are mixed evenly in proportion, stirred while keeping warm, to prepare a polymer clay stabilizer.
[0015] Preferably, the amide containing a carbon-carbon unsaturated bond in step (1) is acrylamide.
[0016] The anionic surfactant in step (1) is 2-methyl-2-acrylamidopropanesulfonic acid.
[0017] The biologically active compound in step (1) is dimethyldiallylammonium chloride.
[0018] The ketone compound in step (1) is 1-vinyl-2-pyrrolidone.
[0019] The initiator in step (1) is a mixture of ammonium persulfate and sodium bisulfite, wherein 40-50 wt% is ammonium persulfate and the remainder is sodium bisulfite.
[0020] Preferably, in step (1), the carbon-carbon unsaturated bond-containing amide, anionic surfactant, bioactive compound, ketone compound and initiator are uniformly mixed in a mass ratio of (2.72-2.76):1:(0.505-0.509):(0.025-0.029):0.024.
[0021] Preferably, the heating reaction in step (1) is carried out under a nitrogen atmosphere at a temperature of 43 to 47° C. for 3.5 to 4.5 hours.
[0022] The recrystallization in step (1) is performed at least three times using anhydrous ethanol.
[0023] Preferably, the amino compound in step (2) is monoethylamine.
[0024] The epoxy hydrocarbon compound in step (2) is epichlorohydrin.
[0025] In step (2), the substrate precursor, the amino compound and the epoxy hydrocarbon compound are uniformly mixed in a mass ratio of 2.2: (0.71-0.75): (0.95-1.05).
[0026] Preferably, the step (2) of preparing the polymer substrate comprises reacting at a temperature of 2 to 5° C. for 6 to 8 hours, dissolving the crude product after the reaction in anhydrous ethanol, and recrystallizing at least three times in acetone and drying.
[0027] Preferably, the ammonium salt in step (3) is acryloyloxyethyltrimethylammonium chloride.
[0028] The metal ion chelating agent in step (3) is diethyltriaminepentaacetic acid.
[0029] The azo initiator in step (3) is azobisisobutylamidine hydrochloride.
[0030] In step (3), the ammonium salt, metal ion chelating agent and azo initiator are uniformly mixed in a mass ratio of 10: (0.04-0.06): 0.1.
[0031] Preferably, the preparation of the modified liquid in step (3) is carried out by heat-preserving polymerization at a temperature of 45 to 65°C for 2.5 to 3.5 hours.
[0032] Preferably, in step (4), the polymer substrate and the modified liquid are uniformly mixed in a mass ratio of 1: (0.5-0.7).
[0033] In step (4), the polymer clay stabilizer is prepared by heat-polymerizing at a temperature of 55 to 65° C. for 3 to 5 hours.
[0034] A polymer clay stabilizer.
[0035] The core of the technology of the present invention is to increase the interaction between ions and mineral particles in the system and improve the adsorption effect of the polymer on the particles by changing the molecular weight of the polymer and introducing new functional groups externally.
[0036] In the scheme of the present invention, the substrate will be hydrolyzed during the application process. The active functional group endpoints exposed after hydrolysis can form a new polymer structure through a new polycondensation reaction. At the same time, they can also react with the hydroxyl groups on the outer surface of the mineral particles to change the surface properties of the particles, modify the hydrophilic surface to make it lipophilic, and thus inhibit the expansion of the particles. In addition, since the lattice layers of clay mineral particles will produce cations that detach and adhere, causing the mineral itself to show electrical properties, the polymer prepared by the present invention can further penetrate into the mineral layers. Dimethyldiallyl ammonium chloride can induce some high-valent cations to be replaced by low-valent cations, resulting in excessive negative charges in the lattice, further forming permanent negative charges. At this time, the cations of the organic polymer species are adsorbed on the surface of the crystal layer during the formation of the clay mineral particles, forming a layer of charge film. The film structure can neutralize the negative charge carried by the original negative charge, so that the clay mineral is uncharged as a whole. When encountering water during the mining process, some of the cations attached to the outside of the lattice layer will be released, so that they offset the compensation effect of the cations and the electrostatic effect is weakened. However, the polymer can form a large number of hydrogen bonds and adsorb on the clay surface after encountering water, and has a good inhibitory ability on the hydration and swelling of the clay. At this time, the polymer is firmly adsorbed on the clay surface through the combined action of electrostatic and hydrogen bonding effects, and the hydrophobic segments on the polymer can enhance the hydrophobicity of the clay mineral surface; at the same time, due to the mutual attraction of opposite charges in the electrostatic effect, the interlayer repulsion is reduced, the distance between the hydration layers is compressed, and the clay particles remain stable.
[0037] Another core of the present invention is to optimize the molecular structure of the polymer to prepare a polymer chain with low molecular weight and high cationicity, thereby improving the adsorption capacity of the polymer and the treatment effect on clay minerals. At the same time, the polymer hydrophobic chain forms a hydrophobic layer to prevent water molecules from invading and reduce clay hydration expansion.
[0038] Through a more in-depth analysis of the properties of clay minerals, it is found that clay minerals have some variable charges. Due to the presence of some hydroxyl groups in the structure of clay minerals, when clay minerals are in an alkaline environment with high pH, a small amount of H + The difference in the types of ions and constituent minerals leads to the difference in the ratio of variable, mobile and transferable charges to non-transferable or transferable charges in the particles, which ultimately results in a small amount of mobile and transferable negative charge in montmorillonite, most of the non-transferable negative charge exists in illite, and kaolinite contains the remaining non-mobile and transferable negative charge.
[0039] In the scheme of the present invention, a large number of positively charged atoms are attached to the polymer chain through the modification of polyacryloyloxyethyl trimethyl ammonium chloride. First, the cations on the polymer chain are firmly anchored on the surface of the clay particles through electrostatic interaction. Then, the polymer uses the strong binding force of hydrogen bonds and the weak attraction of van der Waals forces to construct a dense adsorption layer on the surface of the clay particles that can block the penetration of water molecules. The charge carried by this adsorption layer is complementary to the charge on the outer surface of the clay particles, thereby effectively neutralizing the electrostatic repulsion between them, so that the polymer can be more tightly attached to the clay particles. This tight attachment mechanism not only effectively controls the expansion of the clay, but also significantly inhibits the movement and migration of the particles. At the same time, it shortens the distance between the crystal layers of the clay particles, thereby preventing further penetration and expansion of water molecules. Therefore, the new polymer structure formed by the polycondensation of the polymer after hydrolysis has a large number of adsorption sites. Even if the adsorption effect is partially weakened, the effect on the overall effect is relatively limited, and the stability and effectiveness of the effect can be maintained for a long time.
[0040] In addition, when the polymer provided by the present invention enters the water environment, the charged part on the polymer chain will be dispersed in the water to construct a colloidal environment. Due to electrostatic attraction, ions of opposite charges (counter ions) in the water tend to approach the surface, while the thermal motion of the ions causes them to diffuse away from the surface; ions of the same charge (co-charged ions) in the water have opposite movement trends. When the electrostatic attraction and thermal motion are balanced, a diffusion layer mainly composed of counter ions will naturally form on the surface of the clay mineral particles. The number of counter ions in this layer will gradually decrease with the increasing distance from the particle surface, forming an obvious concentration gradient. At the same time, the change trend of co-charged ions is opposite to that of counter ions, that is, their number increases with the increase of the distance from the surface, showing a diffuse distribution state. In the condensation process of the new polymer structure, most clay mineral particles are close together and the charged properties are superimposed on each other to form a compact layer. The compact layer that appears at this time and the above-mentioned diffusion layer together constitute a diffuse double layer structure. Under the influence of the diffuse double layer structure, the phenomenon of reservoir water-sensitive damage can be effectively avoided, and the application conditions of clay stabilizers can be expanded.
[0041] The advantages of the present invention are as follows: the present invention adjusts the molecular weight of the polymer and introduces new functional groups to enhance the interaction between ions and mineral particles, improve the adsorption effect, and give it excellent anti-swelling, flocculation and surface activity at low concentrations; optimizes the polymer structure, prepares low molecular weight and high cationic polymer chains, and improves the adsorption capacity and clay mineral treatment effect; at the same time, the hydrophobic chain forms a hydrophobic layer to prevent the invasion of water molecules, reduce clay hydration expansion, and avoid water-sensitive damage to the reservoir. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0043] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0044] Example 1: A method for preparing a polymer clay stabilizer, the method comprising: (1) uniformly mixing acrylamide, 2-methyl-2-acrylamidopropanesulfonic acid, dimethyldiallylammonium chloride, 1-vinyl-2-pyrrolidone and an initiator in a mass ratio of 2.72:1:0.505:0.025:0.024, heating the mixture for 4.5 h at a temperature of 43°C in a nitrogen atmosphere, filtering, recrystallizing the mixture three times with anhydrous ethanol, and drying the mixture to prepare a substrate precursor; the initiator is a mixture of ammonium persulfate and sodium bisulfite, the initiator comprising 45 wt% of ammonium persulfate and the remainder of sodium bisulfite.
[0045] (2) The substrate precursor, monoethylamine and epichlorohydrin were uniformly mixed in a mass ratio of 2.2:0.71:0.95, and continuous stirring was immediately started. The mixture was reacted at a temperature of 2°C for 8 h. The crude product after the reaction was dissolved in anhydrous ethanol, and recrystallized three times with acetone, and dried for 24 h to prepare a polymer substrate.
[0046] (3) Acryloyloxyethyl trimethyl ammonium chloride, diethyl triamine pentaacetic acid and azobisisobutyl amidine hydrochloride were uniformly mixed in a mass ratio of 10:0.04:0.1, and the mixture was polymerized at 45°C for 3.5 h to prepare a modified solution.
[0047] (4) The polymer base material and the modified liquid were mixed evenly in a mass ratio of 1:0.5, and the mixture was polymerized at 55 °C for 5 h to prepare a polymer clay stabilizer.
[0048] The clay stabilizer prepared in the example was subjected to performance testing, and the specific characterization results are as follows.
[0049] Anti-swelling rate test: weigh 0.5 g bentonite, add 10 mL deionized water, shake to volume, let stand at room temperature for 2 hours, centrifuge at 1500 r / min for 15 minutes, and record the volume of bentonite. ; Weigh 5.0 g bentonite and 0.25 g clay stabilizer, add 10 mL deionized water, shake to volume, let stand at room temperature for 2 h, centrifuge at 1500 r / min for 15 min, and record the volume of bentonite ; Weigh 0.5 g of bentonite, add 10 mL of kerosene, shake to volume, let stand at room temperature for 2 h, centrifuge at 1500 r / min for 15 min, and record the volume of bentonite , and calculate the anti-swelling rate of clay stabilizer according to the following formula.
[0050] .
[0051] Where: η——anti-swelling rate of clay stabilizer, %.
[0052] ——The volume of bentonite in kerosene, mL.
[0053] ——The volume of bentonite in clay stabilizer, mL.
[0054] ——The volume of bentonite in clean water, mL.
[0055] Washing resistance test: Take out the clay stabilizer test sample group in the above test, pour out the supernatant in the centrifuge tube, add deionized water to 10 mL, stir well, let it stand at room temperature for 2 hours, centrifuge it in a centrifuge at 1500 r / min for 15 minutes, and finally measure and record the volume of bentonite in the centrifuge tube. , and the water resistance of clay stabilizer is calculated using the following formula.
[0056] .
[0057] Where: N——water resistance of clay stabilizer, %.
[0058] ——The volume of bentonite in clay stabilizer, mL.
[0059] ——The expansion volume of bentonite after washing, mL.
[0060] ——The volume of bentonite in clean water, mL.
[0061]
[0062] In addition, referring to the detection method in SY / T 5370-2018, the surface and interfacial tension of the clay stabilizer prepared in the example were measured at room temperature using the ring method. At the same time, the surface tension of the clay stabilizer prepared in the example was measured in an environment of a temperature of 120°C and a pressure of 24 MPa. The specific characterization results are as follows.
[0063]
[0064] In addition, the weather resistance of the clay stabilizer prepared in the example was tested, and the characterization results are as follows.
[0065] Temperature resistance test: Referring to the above clay stabilizer evaluation method, the anti-swelling rate of the clay stabilizer solution of the same concentration at 20 ℃, 35 ℃, 50 ℃, 75 ℃, 90 ℃, 130 ℃, and 150 ℃ was measured. The specific test steps are as follows: accurately weigh the bentonite and 1 wt% clay stabilizer solution and mix them evenly, let them stand in a water bath at the required temperature of the test environment for 2 hours, and use the centrifugal method to detect its anti-swelling rate after cooling, and compare the results. The specific characterization results are as follows.
[0066]
[0067] Salt resistance test: Calcium chloride: magnesium chloride: sodium chloride are evenly mixed in a mass ratio of 3:2:15, and standard saline solutions with different mineralization degrees (4000, 8000, 12000, 16000, 20000, 24000, 28000, 35000, 40000 mg / L) are prepared. A solution with a clay stabilizer concentration of 2.0% is prepared using standard saline solutions of different concentrations and standard salt water of different concentrations as solvents. Referring to the above-mentioned anti-swelling performance test, the anti-swelling effect of the clay stabilizer is determined, and the characterization results are as follows.
[0068]
[0069] Acid and alkali resistance test: Accurately prepare hydrochloric acid and sodium hydroxide solutions with a mass fraction of 25.0%, adjust the 2.0% clay stabilizer solution to the pH required for the test (1, 3, 5, 7, 9, 11, 13), refer to the above anti-swelling performance test, and determine the anti-swelling effect of the clay stabilizer. The characterization results are as follows.
[0070]
[0071] Analysis of the above characterization results shows that the clay stabilizer prepared in the example has excellent anti-swelling performance, outstanding water resistance, and can still maintain more than 50% of the stabilizer properties in a high temperature and high pressure environment. In addition, the clay stabilizer prepared in the example has strong weather resistance under the optimization of the modified liquid.
[0072] On the other hand, the clay stabilizer of the present invention exhibits better anti-swelling performance in a salt solution system and an acidic solution system than in a conventional system, which is mainly due to the higher stability of the colloidal environment constructed by the clay stabilizer in the acid and salt system.
[0073] Example 2: A method for preparing a polymer clay stabilizer, the method comprising: (1) uniformly mixing acrylamide, 2-methyl-2-acrylamidopropanesulfonic acid, dimethyldiallylammonium chloride, 1-vinyl-2-pyrrolidone and an initiator in a mass ratio of 2.74:1:0.507:0.027:0.024, heating the mixture for 4 h at a temperature of 45°C in a nitrogen atmosphere, filtering, recrystallizing the mixture three times with anhydrous ethanol, and drying the mixture to prepare a substrate precursor; the initiator is a mixture of ammonium persulfate and sodium bisulfite, the initiator comprising 45 wt% of ammonium persulfate and the remainder of sodium bisulfite.
[0074] (2) The substrate precursor, monoethylamine and epichlorohydrin were uniformly mixed in a mass ratio of 2.2:0.73:1, and continuous stirring was immediately started. The mixture was reacted at 4°C for 7 h. The crude product after the reaction was dissolved in anhydrous ethanol, and recrystallized three times with acetone. The mixture was dried for 24 h to prepare a polymer substrate.
[0075] (3) Acryloyloxyethyl trimethyl ammonium chloride, diethyl triamine pentaacetic acid and azobisisobutyl amidine hydrochloride were uniformly mixed in a mass ratio of 10:0.05:0.1, and the mixture was polymerized at 55°C for 3 h to prepare a modified solution.
[0076] (4) The polymer base material and the modified liquid were mixed evenly in a mass ratio of 1:0.6, and the mixture was polymerized at 60 °C for 4 h to prepare a polymer clay stabilizer.
[0077] The clay stabilizer prepared in the example was subjected to the same performance test as in Example 1, and the specific characterization results are as follows.
[0078]
[0079]
[0080]
[0081]
[0082]
[0083] Analysis of the above characterization results shows that the clay stabilizer prepared in the example has excellent anti-swelling performance, outstanding water resistance, and can still maintain more than 50% of the stabilizer properties in a high temperature and high pressure environment. In addition, the clay stabilizer prepared in the example has strong weather resistance under the optimization of the modified liquid.
[0084] Example 3: A method for preparing a polymer clay stabilizer, the method comprising: (1) uniformly mixing acrylamide, 2-methyl-2-acrylamidopropanesulfonic acid, dimethyldiallylammonium chloride, 1-vinyl-2-pyrrolidone and an initiator in a mass ratio of 2.76:1:0.509:0.029:0.024, heating the mixture for 3.5 h at a temperature of 47°C in a nitrogen atmosphere, filtering, recrystallizing the mixture three times with anhydrous ethanol, and drying the mixture to prepare a substrate precursor; the initiator is a mixture of ammonium persulfate and sodium bisulfite, the initiator comprising 45 wt% of ammonium persulfate and the remainder of sodium bisulfite.
[0085] (2) The substrate precursor, monoethylamine and epichlorohydrin were mixed evenly in a mass ratio of 2.2:0.75:1.05, and continuous stirring was immediately started. The mixture was reacted at a temperature of 5°C for 6 h. The crude product after the reaction was dissolved in anhydrous ethanol, and recrystallized three times with acetone, and dried for 24 h to prepare a polymer substrate.
[0086] (3) Acryloyloxyethyl trimethyl ammonium chloride, diethyl triamine pentaacetic acid and azobisisobutyl amidine hydrochloride were uniformly mixed in a mass ratio of 10:0.06:0.1, and the mixture was polymerized at 65°C for 2.5 h to prepare a modified solution.
[0087] (4) The polymer base material and the modified liquid were mixed evenly in a mass ratio of 1:0.7, and the mixture was polymerized at 65 °C for 3 h to prepare a polymer clay stabilizer.
[0088] The clay stabilizer prepared in the example was subjected to the same performance test as in Example 1, and the specific characterization results are as follows.
[0089]
[0090]
[0091]
[0092]
[0093]
[0094] Analysis of the above characterization results shows that the clay stabilizer prepared in the example has excellent anti-swelling performance, outstanding water resistance, and can still maintain more than 50% of the stabilizer properties in a high temperature and high pressure environment. In addition, the clay stabilizer prepared in the example has strong weather resistance under the optimization of the modified liquid.
[0095] Comparative Example 1: A commercially available organic cationic polymer clay stabilizer, whose main components are epichlorohydrin and dimethylamine, and polyethyleneimine as a cross-linking agent. The commercially available organic cationic polymer clay stabilizer was subjected to the same performance test as Example 1, and the characterization results are as follows.
[0096]
[0097]
[0098]
[0099]
[0100]
[0101] Analysis of the above characterization results shows that commercially available organic cationic polymer clay stabilizers have stronger anti-swelling effect and water resistance, but the anti-swelling effect of commercially available clay stabilizers decreases significantly when the temperature exceeds 90 °C, and the anti-swelling effect also decreases significantly in strong acid and alkali environments. In actual operation, commercially available polymer clay stabilizers will change the wettability of the rock surface after being injected into the formation to achieve the purpose. Cationic surfactants can make the rock oil-wet and prevent water from entering the clay, but at the same time, due to the large relative molecular mass, cationic polymers will not only not have a good anti-swelling effect, but will cause pore throat blockage due to excessive polymer viscosity, destroy permeability, and affect crude oil recovery.
[0102] Comparative Example 2: A commercially available inorganic polymer clay stabilizer, whose main component is aluminum chlorohydrate, was subjected to the same performance test as Example 1, and the characterization results are as follows.
[0103]
[0104]
[0105]
[0106]
[0107]
[0108] Analysis of the above characterization results shows that a commercially available inorganic polymer clay stabilizer is not resistant to water erosion, is easily affected by the external environment, and can only effectively prevent swelling in a neutral or slightly acidic environment. Further research on commercially available stabilizers shows that the stabilizer will decompose and form complexes in water, producing a large number of hydroxyl hydrated cations. The ions extend the chain to both ends through the action of hydroxyl bridges to produce multi-core polymers, gradually forming longer molecular chains, aggregating multiple mineral particles, reducing the mutual repulsion between particles, and having a certain stabilizing effect on clay. However, when the action environment is not neutral, the molecular chain structure is not easy to construct, resulting in higher requirements for the construction environment.
[0109] Comparative Example 3: A method for preparing a polymer clay stabilizer, wherein the specific preparation method is the same as that of Example 1, except that the substrate modification process unique to the present invention is not used in the comparative example, that is, the substrate precursor referred to in step (1) is directly used as the substrate, and monoethylamine and epichlorohydrin are no longer used for modification. The preparation method of the polymer clay stabilizer is carried out, and the clay stabilizer prepared in the comparative example is tested for performance in the same manner as in Example 1, and the characterization results are as follows.
[0110]
[0111]
[0112]
[0113]
[0114]
[0115] Analysis of the above characterization results shows that since the substrate was not preliminarily modified in this example, the various test performances of the clay stabilizer prepared in this example were reduced. After further research, if the substrate is not preliminarily modified in the scheme of the present invention, the stability inside the substrate will be greatly reduced, especially in a high temperature environment, the epoxy group has high activity and is more susceptible to ring-opening polymerization, resulting in more monomers being connected to a single molecular chain, resulting in a decrease in the cationic degree of the system, causing the polymer to lose its inhibitory effect.
[0116] Comparative Example 4: A method for preparing a polymer clay stabilizer, wherein the specific preparation method is the same as that of Example 1, except that the specific modified liquid of the present invention is not prepared and used. That is, the polymer substrate referred to in step (2) is directly used as a clay stabilizer. The clay stabilizer prepared in the comparative example is tested for performance in the same manner as in Example 1, and the characterization results are as follows.
[0117]
[0118]
[0119]
[0120]
[0121]
[0122] Analyzing the above characterization results, since the substrate was not modified in this example, the various test performances of the clay stabilizer prepared in this example were reduced, especially the performance retention and water resistance in high humidity environment were particularly obvious. After further in-depth research, in the scheme of the present invention, when the mineral is in a low-mineralization aqueous solution environment, the cation concentration of the modified polymer chain will be slightly increased compared to its concentration in the bulk solution environment. The result is that there will be a significant osmotic pressure difference between the liquid phase outside the mineral layer and the liquid phase inside the layer and the oil and gas layer. Under the action of the pressure difference, water molecules will tend to move and diffuse to the outer surface of the clay mineral crystal layer. At the same time, in the bulk aqueous solution in the mineral layer, some cations originally attached to the surface of the clay mineral will also diffuse. This series of processes together lead to the formation of a diffuse double layer. The compact layer formed by the new polymer structure constructed by the polymer in the water system during the polycondensation process can effectively avoid the phenomenon of water-sensitive damage to the reservoir and expand the application conditions of the clay stabilizer.
Claims
1. A method for preparing a polymer clay stabilizer, characterized in that: The method comprises: (1) Mixing an amide containing a carbon-carbon unsaturated bond, an anionic surfactant, a bioactive compound, a ketone compound and an initiator in a uniform proportion, heating for reaction, filtering for recrystallization, and drying to prepare a substrate precursor; (2) uniformly mixing the substrate precursor, the amino compound and the epoxy hydrocarbon compound in proportion, and continuously stirring to prepare a polymer substrate; (3) Mix the ammonium salt, metal ion chelating agent and azo initiator in proportion, stir and keep warm to prepare a modified solution; (4) uniformly mixing the polymer base material and the modified liquid according to a certain proportion, stirring while keeping warm, to prepare a polymer clay stabilizer; The amide containing a carbon-carbon unsaturated bond in step (1) is acrylamide; The anionic surfactant in step (1) is 2-methyl-2-acrylamidopropanesulfonic acid; The biologically active compound in step (1) is dimethyldiallylammonium chloride; The ketone compound in step (1) is 1-vinyl-2-pyrrolidone; The initiator in step (1) is a mixture of ammonium persulfate and sodium bisulfite, wherein 40-50 wt% is ammonium persulfate and the remainder is sodium bisulfite; In step (1), the carbon-carbon unsaturated bond-containing amide, anionic surfactant, bioactive compound, ketone compound and initiator are uniformly mixed in a mass ratio of (2.72-2.76):1:(0.505-0.509):(0.025-0.029):0.024; The amino compound in step (2) is monoethylamine; The epoxy hydrocarbon compound in step (2) is epichlorohydrin; Step (2) The substrate precursor, amino compound and epoxy hydrocarbon compound are uniformly mixed in a mass ratio of 2.2: (0.71-0.75): (0.95-1.05); The ammonium salt in step (3) is acryloyloxyethyl trimethyl ammonium chloride; The metal ion chelating agent in step (3) is diethyltriaminepentaacetic acid; The azo initiator in step (3) is azobisisobutylamidine hydrochloride; Step (3) The ammonium salt, metal ion chelating agent and azo initiator are uniformly mixed in a mass ratio of 10: (0.04-0.06): 0.1; In step (4), the polymer substrate and the modified liquid are uniformly mixed in a mass ratio of 1: (0.5-0.7).
2. The method for preparing a polymer clay stabilizer according to claim 1, characterized in that: The heating reaction in step (1) is carried out under a nitrogen atmosphere at a temperature of 43 to 47°C for 3.5 to 4.5 hours; The recrystallization in step (1) is performed at least three times using anhydrous ethanol.
3. The method for preparing a polymer clay stabilizer according to claim 1, characterized in that: The step (2) of preparing the polymer substrate is to react at a temperature of 2 to 5° C. for 6 to 8 hours, dissolving the crude product after the reaction in anhydrous ethanol, and recrystallizing at least three times in acetone and drying.
4. The method for preparing a polymer clay stabilizer according to claim 1, characterized in that: The step (3) of preparing the modified liquid is to polymerize the modified liquid at a temperature of 45 to 65°C for 2.5 to 3.5 hours.
5. The method for preparing a polymer clay stabilizer according to claim 1, characterized in that: The step (4) of preparing the polymer clay stabilizer is carried out by heat-preserving polymerization at a temperature of 55 to 65° C. for 3 to 5 hours.
6. A polymer clay stabilizer prepared by the method of any one of claims 1 to 5.
Citation Information
Patent Citations
High-temperature resistant clay stabilizer and preparation method thereof
CN104418984A
Novel powder cationic polymer for preventing clay from hydration swelling
CN104650287A